(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the structure and content of educational programs in Uzbekistan’s vocational education system and the necessity for their improvement. In particular, it proposes the formation of the main components of vocational education programs—qualification requirements, model curricula, and model syllabi—as a unified and integrated document. Furthermore, the current situation is analyzed, and special attention is paid to the necessity to reform the content and essence of vocational education programs based on the demands of the time, ways to improve based on new approaches relying on foreign experiences, as well as its prospective outcomes.